Analisis Layout Shearwall Terhadap Perilaku Struktur Gedung - Andalas, George; Suyadi, Suyadi; Husni, Hasti Riakara (Universitas Lampung, 2016)
Shearwall is one of alternative solution in planning of building structure for earthquake-resistant. Shearwall is able to affect stiffness of the building structure and provide a structure with good ductility, so as to minimize the damaged caused by earthquake shaking. This study aimed to analyze the positioning of shearwall on a building structure models using non-linear static analysis (Pushover) In the analisys, shearwalls on each models are placed at different position. The performance of the building structure was analyzed using SAP2000 program. The result of the analysis is a form of drift ratio on each model of the buliding structure. From the result obtained drift value ratio on without shearwall model, model 1, model 2, model 3, model 4, model 5, model 6 in the X direction in sequences as follows: 54 x 10-8; 48 x 10-8; 42 x 10-8; 30 x 10-8; 28 x 10-8; 8 x 10-9; 8 x 10-9 . While in the Y direction as follows: 77 x 10-5; 66 x 10-5; 62 x 10-5; 51 x 10-5; 23 x 10-5; 15 x 10-5; 14 x 10-5. So we can conclude that model 6 has better performance compared to other models. Then, the optimum model of positioning ot the shearwalls is model 6. keywords: SAP2000, pushover analysis, shearwall, erathquake load.